Daughters of the desert : stories of remarkable women from Christian, Jewish, and Muslim traditions - Murphy, Claire Rudolf (SkyLight Paths Pub., 2003)
A collection of eighteen true stories about women who played key roles in the development of Judaism, Islam, and Christianity.